Analisis Metadata Pada Literatur Akuntansi Sektor Publik Dan Pengelolaan Aset - Azis, Muh. Irfandy (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This study aims to analyze the distribution patterns of academic documents in the fields of public sector accounting and asset management based on metadata parameters such as publication year, source, author, institutional affiliation, country, document type, and subject area. Using a descriptive approach based on metadata and data from the Scopus database, this research identifies trends, geographical contributions, and the roles of journals and institutions in the development of the literature. The findings reveal a significant increase in publications in this field, especially during the 2020–2025 period, with articles being the dominant document type and Business, Management, and Accounting as the main subject. Australia, Italy, and the United Kingdom are the largest geographical contributors, with the Public Money and Management journal making the most significant contribution. The analysis also highlights the important roles of several key authors and leading institutions, as well as the diversity of contributions from various sources and countries. This research offers both theoretical and practical implications. Theoretically, the metadata analysis provides insights into research distribution, thematic trends, and the potential for cross-institutional collaboration. Practically, the findings support more targeted policy-making in public sector management, including improvements in efficiency and sustainability. Despite limitations in the uneven access to historical data, this study paves the way for future research to explore underexplored areas, subject diversification, and the development of interdisciplinary approaches.